Caminhos para o sucesso: a coalizão e as medidas provisórias no governo Bolsonaro - Bertolazzi, Marina Zen (2024)
Amid debates about the importance of institutional political arrangements for the maintenance and stability of the democratic regime, as well as a perception of the changing views on coalition presidentialism, the challenge faced by presidents in forming and maintaining necessary alliances in Congress stands out. The negotiation power concentrated in the hands of the Executive, a source for obtaining a coalition by using control over the ministerial organization of the government, the power of the agenda, and the decree power as tools for exchanging support, becomes essential for understanding a president's way of governing. The current situation in Brazil, here focused on the government of Jair Bolsonaro, presents challenges to the literature on coalition formation by witnessing a presidential candidate's choice not to officially engage with other parties, and raises questions about the efficacy of coalitions in governance and the way it is conducted. Throughout his government, however, the approach with the suprapartisan group Centrão has attracted attention. Considering his four-year term, this thesis aims to comparatively analyze governance in an isolated government and in a coalition government. The study focuses on the Provisional Presidential Decree presented by the sitting president, observing the impact on legislative success of the conversion of these decrees after obtaining support from 2021 onwards. The results indicate that the approach to parties, especially with the president of the Chamber of Deputies, provided significant support for the deliberation and approval of his decrees, but with an added caveat: the increased prominence of the Legislature and its growing interference in government projects.